ANALISIS KINERJA KEUANGAN DAERAH PEMERINTAH PROVINSI JAWA TIMUR TAHUN ANGGARAN 2010 - 2014 - Ayu Rosida, Siti; Fitrawansyah; Saepudin, Udin (Jurnal Gici Jurnal Keuangan dan Bisnis, 2024)
This research is descriptive in nature, in which this research will be described accordingly with the research results obtained. The purpose of this research is to find out financial performance using the level of regional financial independence, level regional dependency, level of fiscal decentralization, level of effectiveness and level efficiency in the province of East Java Fiscal Year 2010 – 2014. Research results the ratio of the level of regional independence explains that the average level of independence the regional finance of East Java Province during the 2010 - 2014 budget period amounted to 3.27%. According to the regional financial independence assessment criteria is “Very Good” that is, it can be said that they do not have a high dependency on central government through balancing funds. The dependency ratio has an average of –the average percentage is 1%, namely "Very Low" which is East Java Province has been optimal in financing its regional development activities, so that the regions does not depend on government subsidies through balancing funds. Results analysis of the average level of fiscal decentralization in East Java Province the 2010 - 2014 budget amounted to 69.34%. The level of effectiveness has a percentage an average of 113.25%, namely the effectiveness level of "Very Effective". Efficiency ratio regional financial management in East Java Province has an average percentage of 1.46%, namely "efficient", where the government provides incentive funds for realize PAD to the maximum so as to be able to carry out the implementation regional budget properly/efficiently.